Family Medicine Telehealth Clinic With Medical Students - Peterseim, Carolyn (PRiMER, 2020)
COVID-19 has altered clinical clerkships for medical students, providing an opportunity for telehealth with medical students to take center stage in the age of technology. This research brief demonstrates why and how to incorporate medical students into telehealth. For the purposes of clinical students, telehealth is a better educational alternative to in-person patient care than online modules. We performed a successful outpatient family medicine telehealth pilot program at the Medical University of South Carolina (MUSC) that is currently being scaled up to other clerkships. This pilot was very limited in scope, but serves as a scalable model for future telehealth programs and curricula incorporating medical students.